Transformation From Conventional Dissipative Solitons to Amplifier Similaritons in All-Normal Dispersion Mode-Locked Fiber Lasers - Yueqing Du; Xuewen Shu (IEEE Photonics Journal)
We report the numerical demonstration of the transformation from dissipative solitons to amplifier similaritons in an all-normal dispersion ultrafast fiber laser for the first time. Different from the strong spectral filtering as well as large spectral and temporal breathing ratios for the typical amplifier similariton fiber lasers, our case has relatively weak spectral filtering and small spectral and temporal breath ratios (<6) for amplifier similaritons. An intermediate state between the dissipative soliton and amplifier similariton is discovered, which we call “dissipative similariton” considering its shaping mechanism and characteristics. Pulse regime dynamics is thoroughly explored. The chirp evolution together with pulse structures in time and frequency domains can be used to distinguish the three pulse regimes. This paper can enrich the pulse dynamics in all-normal dispersion fiber lasers and help one to properly design high-energy ultrafast laser configurations.